2003
DOI: 10.1093/beheco/arg062
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral ecology of threshold evolution in a polyphenic beetle

Abstract: Facultative expression of alternative male morphologies is thought to allow individual males to select the phenotype with the highest fitness gain given their competitive status relative to other males with which they compete for females. Choice of, or switching between, morphs commonly relies on developmental threshold responses. Evolutionary changes in developmental threshold responses are thought to provide an important avenue for phenotypic diversification and the evolution of morphological and behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(134 citation statements)
references
References 59 publications
8
125
0
1
Order By: Relevance
“…Moczek et al (2002) suggest that the optimal body size at which the switch between two morpho-types occurs may vary as a function of external conditions. Environmental factors that are known to influence allometric functions in beetles are food quality and competition (Emlen, 1997;Moczek, 2002Moczek, , 2003. In Onthophagus, adult body size and male horn morphology are determined by the quality and quantity of the food that the parents supply their larvae (Moczek, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moczek et al (2002) suggest that the optimal body size at which the switch between two morpho-types occurs may vary as a function of external conditions. Environmental factors that are known to influence allometric functions in beetles are food quality and competition (Emlen, 1997;Moczek, 2002Moczek, , 2003. In Onthophagus, adult body size and male horn morphology are determined by the quality and quantity of the food that the parents supply their larvae (Moczek, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The threshold mechanism and the phenotypic alternatives it regulates are thought to be independent modules (Emlen et al, 2005): the threshold body size can therefore be subject to selection through the fitness of the alternative phenotypes (Tomkins & Hazel, 2007) and evolve rapidly. Despite a well developed theoretical background there are only a few studies that empirically assess intra-specific variation in the threshold that regulates male dimorphic traits (Moczek, 2002(Moczek, , 2003Moczek et al, 2002;Tomkins et al, 2004;Hongo, 2007). There are even fewer studies on the plastic responses of thresholds during the course of a season (but see Emlen, 1996Emlen, , 1997 and the ecological factors that influence polyphenism in natural populations are largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, these studies also showed that evolutionary changes in several of its components provided important avenues for evolutionary changes in patterns of horn expression, ultimately driven by population-wide changes in ecological conditions (summarized in Figure 5; Moczek, 2003;Moczek and Nijhout, 2003). However, to fully appreciate how the endocrine regulation of beetle horns links ecological to evolutionary change, we first need to briefly review the behavioral and ecological context in which beetle horns and horned beetles function.…”
Section: The Endocrine Regulation Of Beetle Hornsmentioning
confidence: 99%
“…Any ecological factor that somehow alters the composition of males within a population, or the nature of interactions between males, would be likely to also affect the exact location of the optimal body size threshold. Populations subject to divergent ecologies might then diverge in the exact scaling relationship between body size and horn length (Moczek, 2003).…”
Section: Sexual Selection Evolutionary Endocrinology and The Diversmentioning
confidence: 99%
See 1 more Smart Citation